2018
DOI: 10.1136/bmjopen-2017-020946
|View full text |Cite
|
Sign up to set email alerts
|

Does the performance of five back-associated exercises relate to the presence of low back pain? A cross-sectional observational investigation in regional Australian council workers

Abstract: ObjectivesInvestigate the relationships between the ability/inability to perform five physical test exercises and the presence or absence of low back pain (LBP).SettingRegional Australian council training facility.ParticipantsConsecutive participants recruited during 39 back education classes (8–26 participants per class) for workers in general office/administration, parks/gardens maintenance, roads maintenance, library, child care and management. Total sample (n=539) was reduced through non-consent and insuff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 98 publications
0
2
0
2
Order By: Relevance
“…Our results revealed that physical exercise history decreased the prevalence of MSDs, in particular, the symptoms of the elbow (OR=0.4; CI=0.2, 0.9). Exercise habits significantly affect the health status of the whole musculoskeletal system [30]. A study performed in the hazelnut industry suggested that 88.6% of the workers had no exercise habits and the ratio of LBP was higher in the subjects who did not exercise [23].…”
Section: Discussionmentioning
confidence: 99%
“…Our results revealed that physical exercise history decreased the prevalence of MSDs, in particular, the symptoms of the elbow (OR=0.4; CI=0.2, 0.9). Exercise habits significantly affect the health status of the whole musculoskeletal system [30]. A study performed in the hazelnut industry suggested that 88.6% of the workers had no exercise habits and the ratio of LBP was higher in the subjects who did not exercise [23].…”
Section: Discussionmentioning
confidence: 99%
“…Concurrently, there has been an escalation in imaging, opioid prescription, injections and surgery, with questionable benefit55–57 and higher risks 8 58. Changing physical risk factors like type of movement pattern,59 level of strength and conditioning60 61 and sustained or repeated postures,62 63 are relatively risk free, cost-effective and show great potential. Sleep posture is an example of a sustained physical risk factor that is modifiable 64 65.…”
Section: Discussionmentioning
confidence: 99%
“…4 , 5 kann Patienten gezeigt werden, welche körperlichen Voraussetzungen fehlen, um an das persönliche Ziel zu gelangen. Schließlich gibt es Hinweise darauf, dass bestimmte körperliche Übungen mit dem Auftreten von LBP in Zusammenhang stehen (siehe Testbatterie von Gabel et al 36 ). Ein gezieltes Trainingsprogramm könnte in diesem Fall entsprechende Wirkung zeigen.…”
Section: Diskussionunclassified
“…Bei einer Studie mit Arbeitnehmern, die an einer Rückenschulgruppe teilnehmen, untersuchten Gabel et al [36] den Zusammenhang zwischen der Durchführbarkeit einer bestimmten Testbatterie von 5 Übungen ("Extension in lying", "Squat", "Raise up", "Sit up", "Leg extension") und dem Auftreten von LBP. 94,3 % der Patienten ohne LBP konnten mindestens 4 der 5 Tests durchführen.…”
Section: Auf Körperfunktion Und -Struktur Bezogene Testsunclassified